Effect of nintedanib on airway inflammation in a mouse model of acute asthma. (2nd January 2020) - Lee, Jongmin; Rhee, Chin Kook; Lee, Jong Hyuk; Yoon, Hyon Jee; Kim, In Kyoung; Hur, Jung; Kang, Ji Young; Yoon, Hyoung Kyu; Lee, Sook Young; Kim, Young Kyoon
Abstract: Objective: New treatments are needed for cases of asthma that are refractory to traditional therapies. In this study, we examined the effect of oral nintedanib, an intracellular inhibitor of tyrosine kinases, on airway hyper-responsiveness (AHR) and airway smooth muscle cells, using a mouse model of experimental asthma. Methods: Asthma was experimentally induced in mice via subcutaneous injection of ovalbumin (OVA). A group of saline-injected mice served as a control group. The OVA mice were then divided into four treatment groups according to the dose of nintedanib. AHR was examined via exposure to vaporized methacholine. Airway inflammation was assessed via bronchoalveolar lavage fluid (BALF) cell counts and Th2 cytokine concentrations. Results: Baseline levels of AHR and airway inflammation were higher in OVA mice than in the control group. Treatment with nintedanib lowered AHR, BALF cell counts and BALF cytokine levels in a dose-dependent fashion. The effect of nintedanib was comparable to that of dexamethasone. In particular, treatment with nintedanib lowered the expression of transforming growth factor-β1 and inhibited the expression and phosphorylation of platelet-derived growth factor receptor-β, vascular endothelial growth factor receptor 1 (VEGFR1), VEGFR2, fibroblast growth factor receptor 2 (FGFR2), FGFR3, and extracellular signal-regulated kinase. Conclusions: Nintedanib lowered AHR and the expression of factors associated with airway inflammation and remodeling in a mouse model of experimental asthma. Our results suggest that nintedanib may be useful in the treatment of asthma.